2008
DOI: 10.1097/01.prs.0000304600.23129.d3
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Evidence in Plastic Surgery Research over 20 Years

Abstract: The plastic surgery literature has responded to the demand for more evidence-based medicine, but the rate of change has been slow and the field will likely never enjoy the high level of evidence of medical fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 13 publications
5
70
0
3
Order By: Relevance
“…Other areas of medicine have shown similar trends [8,15,29,33]. Recognition of the importance of high-quality research in performing reliable therapeutic studies seems to have produced a change in behavior.…”
Section: Discussionmentioning
confidence: 83%
“…Other areas of medicine have shown similar trends [8,15,29,33]. Recognition of the importance of high-quality research in performing reliable therapeutic studies seems to have produced a change in behavior.…”
Section: Discussionmentioning
confidence: 83%
“…This is significantly higher than what has been reported in the general plastic surgical literature over the past 20 years (5.1 Plastic and Reconstructive Surgery • January 2012 percent), and in maxillofacial surgery (2 percent). 4,6 The proportion of level I and II studies in aesthetic surgery is on par with surgical specialties such as neurosurgery (16.6 percent) and urology (15.6 percent). 14,15 Specialties that publish a greater proportion of higher level evidence include ophthalmology (26.2 percent), orthopedics (32.1 percent), and otolaryngology (32 percent).…”
Section: Relevant Literaturementioning
confidence: 99%
“…We found that the number of articles reporting P values or confidence intervals grew significantly over the study period, which is consistent with trends observed in other studies of plastic surgery. 9,23 Upon on this study, to make scientific literature more scientific, it is quite meaningful to upgrade the numerous level IV and V studies to level II or III. Level II and III literatures are more scientific.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, patient enrollment, loss to follow-up, and high cost make it difficult to conduct randomized controlled trials. 23,24 Sinno et al 7 hypothesized that the diversity of diagnoses and procedures encountered in plastic surgery and the frequent need to tailor or customize reconstructions for individuals make it harder to conduct high-quality research in plastic surgery than in other surgical specialties such as orthopedic surgery and ophthalmology. It is unclear why level of evidence in the auricular defects literature is lagging behind that of other surgical specialties, and other areas of plastic surgery in particular.…”
Section: Discussionmentioning
confidence: 99%